Influence of off-axis in-plane yarns on the mechanical properties of 3D composites. (July 2017) - Labanieh, Ahmad Rashed; Liu, Yang; Vasiukov, Dmytro; Soulat, Damien; Panier, Stéphane
Abstract: In the current paper, investigations have been carried out on in-plane and out-of-plane mechanical properties of 3D multiaxial woven composites keeping in view three different architectures. The first two architectures constitute of additional bias yarns oriented at +θ° and −θ° along with 0° and 90°, whereas the third comprises of yarns directed at 0° and 90° only. Composites in which the bias yarns accompany the 0° and 90° yarns have improved mechanical properties in comparison to classical 3D orthogonal woven textile composites. In order to demonstrate the influence of off-axis yarns on the mechanical properties, uniaxial tensile (loading-unloading) and short beam shear (SBS) tests were conducted. To measure strain field and record the visual analysis of the cracking processes and de-bonding, all mechanical tests were equipped with Digital Image Correlation (DIC) system. It was concluded based on the experimental results that 3D multiaxial woven composites exhibit enhanced interlaminar shear strength compare to classical 3D-orthogonal composites.